QUALITY 4.0 FRAMEWORK IN THE CONSTRUCTION INDUSTRY IN PALESTINE - Nasreen Abdel Hafeeth Altuhul (My University, 2023)
Abstract Many business sectors have been developed in the current rapidly evolving market while others are lagging behind this development such as the Construction Industry (CI). This study gives an overview for Quality 4.0 concept and investigates the relationship between Contract Management System (CMS) with Quality Management System (QMS) in presence of Quality 4.0 acceptance and implementation (Q4.0) as a mediating variable in the construction contracting companies working in West Bank in Palestine. A conceptual literature-based framework was developed to connect between variables using exploratory research. Structured questionnaire was designed to collect data from a randomly selected sample; 95 responses from contracting Palestinian companies were gathered. Partial least squares structural equation modeling (PLS-SEM) using Smart-PLS software was used to analyze and assess the conceptual framework. The results revealed that CMS and QMS are implemented at a high level in the targeted construction companies. Moreover, Q4.0 technological dimensions are highly accepted by these companies. It has been found that; Claims and Disputes Resolution (CDR), Communication and Relationship (CR), and Contract Risk Management (CRM) followed by financial issues are main contractual management dimensions to be developed in this industry. Additionally, the results confirmed that CMS and Q4.0 have significant positive effect on quality management system. On the other hand, results showed that there is no significant impact of Q4.0 on CMS and no mediation effect of Q4.0 acceptance and implementation on the relationship between CMS and QMS. This study contributes in giving empirical evidence about the relationship between CMS, QMS, Q4.0 and recommends that other studies be done to assess the effect of other variables on QMS and to retest this model with in other industrial sectors with alarger sample size so that the results can be generalized. Keywords: Contract Management System (CMS); Construction Industry (CI); Quality; Quality 4.0 (Q4.0); Quality Management System (QMS).